2007
DOI: 10.1111/j.1750-3841.2007.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Directed Isolation of Compounds from Punica granatum

Abstract: Chemical investigation of the methanolic extract of pomegranate fruit following antibacterial activity directed isolation led to the isolation of pelargonidin-3-galactose, cyanidin-3-glucose, gallic acid, quercetin, and myricetin. All these compounds exhibited substantial activity against species of corynebacteria, staphylococci, streptococci, Bacillus subtilis, Shigella, Salmonella, Vibrio cholera, and Escherichia coli. However, all these compounds were more active against Gram-positive species. On comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 23 publications
8
157
1
2
Order By: Relevance
“…Similar to these findings, Alzoreky (2009) had also observed that pomegranate extracts interfered with bacterial protein secretion. Polyphenols play an important role in protein precipitation and enzyme inhibition of microorganisms (Naz et al 2007;Fan et al 2008). The mechanism responsible for phenolic toxicity to microorganisms was related to reaction with sulphydryl groups of proteins and unavailability of substrates to microorganism (Machado et al 2003;Naz et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to these findings, Alzoreky (2009) had also observed that pomegranate extracts interfered with bacterial protein secretion. Polyphenols play an important role in protein precipitation and enzyme inhibition of microorganisms (Naz et al 2007;Fan et al 2008). The mechanism responsible for phenolic toxicity to microorganisms was related to reaction with sulphydryl groups of proteins and unavailability of substrates to microorganism (Machado et al 2003;Naz et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial activity of rosemary extract (Del Campo et al 2000), garlic extract (Tsao and Yin 2001), grape fruits extract in fish (Cho et al 1990), capsicum extract in raw beef (Monica et al 2003), oregano essential oils in sheep meat (Govaris et al 2010) have been reported. The antimicrobial activity of many plant extracts, traditional spices and essential oils is well documented (Ahmad and Beg 2001;Naz et al 2007;Shan et al 2007;Burt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Probable targets on the microbial cell are surface exposed adhesion molecules, cell wall polypeptides and membrane-bound enzymes. The mechanisms thought to be responsible for the phenolic toxicity towards microorganisms, include enzyme inhibition by the oxidized compounds, possibly through reaction with sulphydryl groups or through more nonspecific interactions with proteins often leading to inactivation of the protein and loss of function [49].…”
Section: Effects Of Juices On Growth Inhibition Kineticsmentioning
confidence: 99%
“…1A. Myr has a variety of pharmacological effects, including anti-bacterial (8), analgesic (8), anti-tumor (9,10), anti-allergic (11)(12)(13), anti-oxidant (14,15), blood sugar-lowering (16) and hepatoprotective actions (17). It also exerts protective effects against cardiovascular diseases, including atherosclerosis (18), ischemia-reperfusion injury (19), myocardial infarction (20) and hypertension (21,22).…”
Section: Introductionmentioning
confidence: 99%